An Alternative Route to Pentavalent Postperovskite - Serena Margadonna (Inorganic Chemistry, 2016)
A novel and advantageous synthetic route to post-perovskite (ppv) has produced the second-only known pentavalent CaIrO3-type structure in a compound where commonly used indicators, such as pseudocubic tilt or tolerance factor, suggest that ppv should not form. In addition to demonstrating that ppv-NaOsO3 can be made from perovskite-type NaOsO3 at 16 GPa and 1135 K, ppv NaOsO3 has also been produced, and recovered, from a cubic KSbO3-containing assemblage, at 6 GPa and 1100 K, from an initial mixed-phase precursor of hexavalent Na2OsO4 and nominally pentavalent KSbO3-like phases. It The latter offers a new lower pressure route to the post-perovskite form – one which completely foregoes any perovskite precursor or intermediate. This work suggests that ppv can be obtained in other KSbO3-like compounds, which lend themselves to technological and synthetic application through their advantageous flexibility towards oxygen content, and cation valences and deficiencies, as well as in otherand chemistries where generalized rules based on the pv structure may not apply, or where no perovskite is known. One more obvious consequence of our second route is that perovskite formation may even mask and hinder other less extreme chemical pathways to post-perovskite phases.